Factors Affecting Audit Tenure in Food and Beverage Sub-Sector Companies Listed on the Indonesia Stock Exchange In 2019 – 2023 - Anton, Anton; Felisha, Michelle; Febrianto, Fernando; Tjahjana, Dominicus Josephus Swanto (Luxury: Landscape of Business Administration, 2026)
This study investigates the determinants of audit tenure in Food and Beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Specifically, it examines the influence of solvency (Debt to Equity Ratio), profitability (Return on Assets), liquidity (Current Ratio), and firm size (natural logarithm of total assets) on audit tenure. Using purposive sampling, 47 companies were selected, resulting in 235 firm-year observations. The study employs multiple linear regression analysis using SmartPLS 4. The findings indicate that solvency has a positive but statistically insignificant effect on audit tenure, while profitability shows a negative but insignificant relationship. In contrast, liquidity and firm size exhibit a significant negative effect on audit tenure, suggesting that financially stronger and larger firms tend to experience shorter audit tenure periods. However, the model explains only 6% of the variation in audit tenure, indicating that other factors beyond the variables examined may play a more substantial role. This research contributes to the literature on audit timeliness and corporate financial characteristics in emerging markets.